Experiences of Treatment-Seeking Children and Young People Following Parental Intimate Partner Homicide - Soydas, Suzan (Homicide studies, 2025)
This study provided a detailed description of the experiences of 60 treatment-seeking children and young people following parental intimate partner homicide (PIPH) in the United Kingdom, and evaluated the potential effectiveness of the traumatic grief focused cognitive behavioral therapy they received. A paired samples t-test showed that mean pre-and post-treatment posttraumatic stress scores decreased significantly, with a large effect size. Reliable change indices indicated that 75% improved and 25% remained unchanged. Despite the severe consequences for children and young people following PIPH and the great variability in their experiences, results promisingly show that they may benefit from treatment.